Structural process and testing of tunneling attitude sensor based on gravity gradient torque measurements. (11th November 2021) - Yalu, Cao; Jiahao, Zhao; Fei, Xing; Zheng, You
Abstract: The function of determining the orientation of a satellite in orbit is known as attitude determination. Depending on the missions, this important function is typically performed by different optical instruments. Due to the limited field of view, multiple optical sensors are placed in all directions to ensure large coverage. A kind of inertial sensor that uses the gravity gradient torque as a reference for attitude determination was proposed recently. At present, the volume of this kind of sensors is large and the accuracy is not high enough. In this paper, we propose an attitude sensor, which is composed of a barbell-shaped sensitive structure with larger moment of inertia and a small displacement detection module based on the tunneling effect. The sensitive structure is fabricated by silicon-on-glass process based on micro-electro-mechanical system technology. As a result, the sensitive structure has a smaller size, and the accuracy of angle measurement can reach 7.3° (3 σ ) in the range of −20° to +20°.